1997
DOI: 10.1007/bf02495386
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical calculation of a spillover model on a graphite support

Abstract: The simplest quantum-chemical models of hydrogen spillover over a graphite-like surface as a proton or radical have been considered. The condensed planar C24H12 molecule was tzsed as a model surface. The ab initio calctdations of the interaction of hydrogen with the model surface were carried ot:t by the restricted Hartree--gock (tIF) method in the STO-3G and 6-31G" basis sets. The radical hydrogen can not bind to such a surface, whereas tile proton binds to it with an energy release of 186 kcal rod[ -1. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
3
9
1
Order By: Relevance
“…The activation energies were 33.8 and 13.08 kcal/mol, respectively. In contrast to [4], we obtained a negative enthalpy of attachment of atomic hydrogen to the central atoms of the cluster, which amounted to -11.2 kcal/mol and ∆G= -3.37 kcal/mol, which shows that the reaction is favorable. For comparison, the energy of hydrogen detachment from a similar position from [5] is equal to 42 kcal/mol.…”
Section: Migration Of Charged Particlescontrasting
confidence: 60%
See 3 more Smart Citations
“…The activation energies were 33.8 and 13.08 kcal/mol, respectively. In contrast to [4], we obtained a negative enthalpy of attachment of atomic hydrogen to the central atoms of the cluster, which amounted to -11.2 kcal/mol and ∆G= -3.37 kcal/mol, which shows that the reaction is favorable. For comparison, the energy of hydrogen detachment from a similar position from [5] is equal to 42 kcal/mol.…”
Section: Migration Of Charged Particlescontrasting
confidence: 60%
“…Two variants of the hydrogen spillover over a carbon surface are proposed in literature, confirmed by quantum-chemical modeling: migration of a charged [4] and neutral bounded particle [5]. The choice is made in favor of the migration of a charged particle, since the activation energy of this process is close to the experimental.…”
Section: Problem Statementmentioning
confidence: 93%
See 2 more Smart Citations
“…Borisov et al [21] performed ab initio Hartree-Fock (HF/6-31G*) calculations of a model compound, coronene (C 24 H 12 ), having planar graphite-like framework, of a complex of this compound with proton, and of the transition state in proton migration over the model surface [21]. It has been found that the proton affinity of C 24 H 12 is 779 kJ mol -1 and the activation energy of proton transfer between the adjacent carbon atoms of C 24 H 12 is 42 kJ mol -1 , which is very close to the experimentally determined value of 65 kJ mol -1 for the activation energy Е а of hydrogen spillover on the graphite surface [21].…”
mentioning
confidence: 98%